Knowledge and Awareness Level Regarding Stroke Management in Golden Hours among Medical Students in KSA - ,Hatim Saleh M. Karhan, Khames T. Alzahrani, Adnan Ahmed O. Badahdah, Nawaf Ghalib W. Alaklabi, Hajar Ahmed Y. AL Mustanyir, Yousef Mohammed A. Magbool, Najlaa Abdulmajeed M. Ali, Hussain Abdullah M. Alharbi, Sara Ali H. Alasiri, Rahaf Ayoub A. AL Makrami, Ruya Adel A. Abdullah (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Stroke is a serious medical condition brought on by diminished or interrupted blood flow to the brain. To reduce the cognitive and neurological impairment brought on by stroke, early identification and treatment are essential. Strokes cause death or permanent disabilities globally, with Saudi Arabia’s stroke risk increasing, and by 2030, more people are expected to die from stroke-related causes. Objectives: Our aim was to evaluate the Knowledge and Awareness level of Stroke in general, plus its management during the golden hours among Medical Students and interns in Saudi Arabia. Materials and Methods: This was an observational cross-sectional study. The study was conducted in Saudi Arabia from January 2024 to February 2024, targeting medical students and interns. By using the Raosoft calculator, the sample size was estimated, with a confidence level of 95% and a marginal error of 5%, the minimal sample size was 384. Data were collected through an online questionnaire, entered into Microsoft Office Excel Software, and analyzed using IBM Statistical Package for the Social Sciences Statistics for Windows. Results: As regard the knowledge and awareness score about stroke management, there were 58.0% out of 400 participants demonstrated a high level of awareness regarding stroke management within the crucial golden hours. Moreover, 31.5% of respondents exhibited a moderate level of awareness. However, it is worth noting that 10.5% of participants displayed a low level of awareness. Regarding the relation between awareness level of stroke management in golden hours and sociodemographic characteristics, there was a statistically significant relation to college of medicine (P = 0.0001), present year of study (P = 0.017), present GPA (P = 0.018) and if the participant had enrolled in neurology training before (P = 0.027). It also shows a statistically insignificant relation to gender and age. Conclusion: The study revealed that there is a relatively high level of awareness regarding stroke management within the crucial golden hours, with 58.0% of participants demonstrating a good understanding. This is a positive indication of knowledge among a significant portion of the surveyed population. However, there is still room for improvement as 31.5% showed a moderate level of awareness, and 10.5% displayed a low level of awareness. Comparisons with other studies globally and within Saudi Arabia suggest that awareness levels vary, indicating a need for ongoing educational programs to enhance knowledge about stroke management and the importance of timely interventions.